Compound having phenanthroline structure, and organic electroluminescent device and display device comprising same

By introducing electron-absorbing groups and multiple nitrogen and oxygen atoms into n-type charge generation materials and using aryl substituents, the problems of high driving voltage and short life in stacked OLED devices are solved, and lower driving is achieved Voltage and higher electronic transmission capability and stability.

CN119219700AActive Publication Date: 2024-12-31SHIJIAZHUANG CHENGZHI YONGHUA DISPLAY MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411729864.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-31
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing n-type charge generation materials have a high driving voltage in stacked OLED devices, which is difficult to meet the needs of reducing driving voltage and extending life.

Method used

A compound with a phenanthroline structure is developed to reduce the HOMO energy level of the material by introducing electron-giver group R1 and multiple nitrogen and oxygen atoms, and improve intermolecular stacking through aryl substituents to improve electron transport capability.

Benefits of technology

It significantly reduces the driving voltage, extends the device life, and improves the electronic transmission capability and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219700A_ABST
    Figure CN119219700A_ABST
Patent Text Reader

Abstract

The invention discloses a compound with a phenanthroline structure, and an organic electroluminescent device and a display device comprising the same. The compound is selected from a structure as shown in a formula I in the specification. By introducing an electron withdrawing group R1, the material has deeper HOMO, especially when pyrimidine and other substituents containing multiple nitrogen atoms are used, the HOMO energy level of the material is significantly reduced, and the lower HOMO energy level can prevent aging of an electron transport layer caused by hole invasion, and prolong the service life of a device. Meanwhile, more N atoms are introduced, and hydrogen bonds are formed through N or O and hydrogen atoms, so that the intermolecular stacking condition of the material can be improved, and the electron transmission capability of the material is improved and the driving voltage is reduced through regular arrangement of the material. And # imgabs0 # I is adopted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of OLED, and specifically comprises a compound with a phenanthroline structure and an organic electroluminescent device and a display device comprising the compound. Background Art

[0002] An OLED device formed by connecting multiple OLED light-emitting units in series is called a stacked OLED device. In a stacked OLED device, two independent light-emitting units are connected in series through a charge generation layer (CGL), which is usually constructed in the form of a pn structure. Compared with single-unit devices, stacked devices often have higher current efficiency and luminous brightness. However, with the growing demand for stacked devices to reduce driving voltage and increase life, there is an urgent need to develop CGL materials with better performance suitable for stacked devices. Early n-CGL materials were based on a phenanthroline structure, which had a good electron transport effect, but it was still difficult to meet people's needs.

[0003] The current n-type charge generation materials are mainly selected from the existing electron transport layer materials. There are often problems with the energy level matching of such materials with the metals doped in the n-type charge generation materials or the p-type charge generation materials, resulting in a high driving voltage. Therefore, it is very necessary to develop new charge generation layer materials with higher performance to improve the performance of organic light-emitting devices. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a compound having a phenanthroline structure and an organic electroluminescent device and a display device comprising the compound.

[0005] To achieve the above objectives, the technical solutions adopted by the present invention include: The first aspect of the present invention provides a compound having a phenanthroline structure, wherein the compound is selected from the structure shown in the following formula I: I; Wherein, the ring A, ring B, and R2 are each independently selected from any one of phenyl, biphenyl, or naphthyl; The R1 is selected from one of the following structures: , , , , , , , , , , , , ; In Formula I, at least one hydrogen may be substituted with deuterium, and at least one nitrogen may be substituted with nitrogen-15 (i.e. 15 N) substituted, at least one oxygen may be replaced by oxygen-17 (i.e. 17 O) or oxygen-18 (i.e. 18 O) substitution, at least one carbon may be substituted by carbon-13 (i.e. 13 C) Replacement.

[0006] Furthermore, the structure represented by Formula I is selected from one of the structures represented by Formula I-1 to Formula I-4 below: I-1, I-2, I-3, I-4.

[0007] Further, the R1 is selected from one of the following structures: , , , , , , , , , , , , , , .

[0008] Further, the R1 is selected from one of the following structures: , , .

[0009] Further, the R2 is selected from one of the structures shown below: , , , , , , .

[0010] Further, the compound is selected from one of the structures shown below: .

[0011] The second aspect of the present invention provides a use of the compound as described above in preparing an organic electroluminescent device.

[0012] The third aspect of the present invention provides an organic electroluminescent device, comprising an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more compounds as described above.

[0013] Furthermore, the charge generation region includes an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer includes one or more compounds as described above.

[0014] A fourth aspect of the present invention provides a display device, comprising the organic electroluminescent device as described above.

[0015] Beneficial effects of the present invention: The present invention introduces an electron-withdrawing group R1 to make the material have a deeper HOMO. In particular, when using a substituent containing multiple nitrogen atoms such as pyrimidine, the HOMO energy level of the material is significantly reduced. The lower HOMO energy level can prevent the electron transport layer from being invaded by holes and causing aging, thereby extending the life of the device. At the same time, the introduction of more N atoms and oxygen atoms can improve the intermolecular stacking of the material through the formation of hydrogen bonds between N or O and hydrogen atoms, and through the regular arrangement of the material, the material's electron transport capacity is improved, and the driving voltage is reduced.

[0016] In addition, it was found that if the phosphonyl group or pyrimidine is directly connected to the phenanthroline structure, the combined effect of multiple electron-withdrawing structures will sharply reduce the dissociation energy of the connected single bond, resulting in a poor lifetime. This situation can be improved by introducing aromatic groups such as phenyl or naphthyl between the phosphonyl group or pyrimidine and the phenanthroline structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention. DETAILED DESCRIPTION

[0018] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.

[0019] The compounds of the present invention are suitable for use in light-emitting elements, display panels and electronic devices, and are particularly suitable for use in organic electroluminescent devices. The electronic device of the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED). The schematic structural diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.

[0020] Experimental Section In order to understand the content of the present invention more clearly, the luminescent characteristics of the compound, the preparation method of the compound and the device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of an embodiment of the present invention. However, it should be noted that the synthetic method of the compound of an embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.

[0021] Intermediate Synthesis Example

[0022] Sub-1 (33.8 g, 100 mmol), Sub-2 (40.4 g, 100 mmol) and potassium carbonate (16.6 g, 120 mmol) were added to a mixed solution of 500 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (3.5 g, 3 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified using a petroleum ether: dichloromethane = 10:1 (V / V) column to obtain product B1: 27.8 g, yield: 52%, MS (m / z) (M+): 535.

[0023] Synthesis Example 1

[0024] A1 (6.6 g, 20 mmol), B1 (10.7 g, 20 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 300 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by column separation using petroleum ether: dichloromethane = 10:1 (V / V), and finally the product C1: 8.6 g, yield: 66%, MS (m / z) (M+): 661.

[0025] Synthesis Example 2

[0026] Using the same method as in Synthesis Example 1, A2 (8.7 g, 20 mmol) and B2 (10.7 g, 20 mmol) were used to replace A1 and B1, and finally product C2 was obtained: 9.3 g, yield: 61%, MS (m / z) (M+): 765.

[0027] Synthesis Example 3

[0028] Using the same method as in Synthesis Example 1, A3 (5.6 g, 20 mmol) and B3 (10.7 g, 20 mmol) were used to replace A1 and B1, and finally product C3 was obtained: 7.2 g, yield: 59%, MS (m / z) (M+): 611.

[0029] Synthesis Example 4

[0030] Using the same method as in Synthesis Example 1, A4 (8.2 g, 20 mmol) and B4 (10.7 g, 20 mmol) were used to replace A1 and B1, and finally the product C4 was obtained: 8.7 g, yield: 59%, MS (m / z) (M+): 737.

[0031] Synthesis Example 5

[0032] Using the same method as in Synthesis Example 1, A5 (7.2 g, 20 mmol) and B5 (10.7 g, 20 mmol) were used to replace A1 and B1, and finally product C5 was obtained: 10.9 g, yield: 79%, MS (m / z) (M+): 687.

[0033] Synthesis Example 6

[0034] The same method as in Synthesis Example 1 was used to replace A1 and B1 with A6 (6.6 g, 20 mmol) and B6 (10.7 g, 20 mmol) to finally obtain product C6: 6.7 g, yield: 51%, MS (m / z) (M+): 661.

[0035] Synthesis Example 7

[0036] Using the same method as in Synthesis Example 1, A7 (5.6 g, 20 mmol) and B7 (12.2 g, 20 mmol) were used to replace A1 and B1, and finally product C7 was obtained: 9.1 g, yield: 66%, MS (m / z) (M+): 687.

[0037] Synthesis Example 8

[0038] Using the same method as in Synthesis Example 1, A8 (5.6 g, 20 mmol) and B8 (11.7 g, 20 mmol) were used to replace A1 and B1, and finally product C8 was obtained: 9.2 g, yield: 70%, MS (m / z) (M+): 661.

[0039] Synthesis Example 9

[0040] Using the same method as in Synthesis Example 1, A9 (9.7 g, 20 mmol) and B9 (10.7 g, 20 mmol) were used to replace A1 and B1, and finally the product C9 was obtained: 11.9 g, yield: 73%, MS (m / z) (M+): 814.

[0041] Synthesis Example 10

[0042] The same method as in Synthesis Example 1 was used to replace A1 and B1 with A10 (7.6 g, 20 mmol) and B10 (10.7 g, 20 mmol), and finally the product C10 was obtained: 8.9 g, yield: 63%, MS (m / z) (M+): 712.

[0043] Synthesis Example 11

[0044] Using the same method as in Synthesis Example 1, A11 (7.9 g, 20 mmol) and B11 (10.7 g, 20 mmol) were used to replace A1 and B1, and finally product C11 was obtained: 8.7 g, yield: 60%, MS (m / z) (M+): 726.

[0045] Comparative Examples 1-5 Some of the compounds developed in the research have the following structures:

[0046] Material properties The service life of OLED is determined by the stability of the chemical bond energy of the material. The higher the chemical bond energy, the more likely the material will continue to decompose when it is heated and evaporated and when the OLED is powered on. The strength of the chemical bond can be measured by the bond dissociation energy (BDE). The smaller the bond dissociation energy, the weaker the bond and the more unstable the compound. Using Orca software, the B3LYP / 6-31G(d) method is used to calculate the dissociation energy of each chemical bond. The higher the dissociation energy, the more stable the chemical bond in the structure. The stability of the material is evaluated by comparing the minimum dissociation energy of chemical bonds between different structures.

[0047] The HOMO energy level of the material was tested using the cyclic voltammetry method. The cyclic voltammetry test was performed using the CS350H electrochemical workstation of Coster Instrument Co., Ltd., with tetrabutyl hexafluorophosphate as the electrolyte dissolved in a dichloromethane solution; the measurement was performed using a three-electrode assembly (working electrode and counter electrode: Pt wire, reference electrode: Pt wire) at room temperature in a nitrogen atmosphere, and ferrocene was used as an internal standard to calibrate the HOMO data for the saturated calomel electrode (SCE). The deeper HOMO energy level of nCGL can effectively reduce the migration of holes to the nCGL layer during the charge separation process, improve the charge separation efficiency, reduce the driving voltage, and improve the stability of the material.

[0048] The sample to be tested was deposited on a glass substrate with a thickness of 10 nm. The birefringence of the sample film was tested using an M-2000VI ellipsometer. The molecular orientation was evaluated by detecting the extinction coefficients ke and ko in the vertical and horizontal directions of the sample. The degree of order S is a parameter that characterizes the molecular orientation and is defined as follows:

[0049] Among them, the value of S is between -0.5 and 1. When the value of S is 0, it means that the molecules are randomly distributed. When the value of S is 1, it means that the molecules are completely vertically arranged. The closer the value of S is to -0.5, the higher the molecular orientation is, and the more conducive it is to the transmission of electrons between materials.

[0050] The results are shown in Table 1.

[0051] Table 1

[0052] It can be seen from the above table that when there are more nitrogen atoms in the molecule, the lone pair of electrons of the N atom forms hydrogen bonds with adjacent molecules, which contributes to the regular arrangement of molecules and improves the molecular orientation. Compared with Comparative Example 2, after adding the aryl phosphine oxide substituent, the molecular orientation is further improved due to the effect of the lone pair of electrons of the oxygen atom. By using pyrimidine, quinazoline, quinoxaline, and other structures, the HOMO energy level is significantly reduced compared to the simple use of pyridine, which can effectively limit the migration of holes to the nCGL material layer and improve the material life. At the same time, by adding a spacer, the material dissociation energy caused by the excessive concentration of electron-withdrawing groups can be effectively improved, and the device life of the material described in this case can be further improved.

[0053] Compared with D1, the compound proposed in this application contains an aromatic phosphine oxide substituent, and the molecular orientation is further improved due to the effect of the lone pair of electrons of the oxygen atom. Compared with D4, the compound proposed in this application contains structures such as pyrimidine, quinazoline, and quinoxaline. Since the lone pair of electrons of the N atom in the molecule can form hydrogen bonds with adjacent molecules, it is helpful to arrange the molecules regularly and improve the molecular orientation; compared with D2 and D5, the compound proposed in this application contains structures such as pyrimidine, quinazoline, and quinoxaline. Compared with the use of pyridine alone, due to the increase of lone pair electrons, the molecular orientation will increase slightly, and the HOMO energy level of the material can be significantly reduced. Fabrication and characterization of OLEDs Device Embodiment The organic electroluminescent device provided by the present invention comprises an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer which are sequentially arranged on a substrate; Further, the first hole transport region includes a hole injection layer, a first hole transport layer and a first electron blocking layer; the first electron transport region includes a first hole blocking layer and a first electron transport layer; the charge generation region includes an n-type charge generation layer and a p-type charge generation layer; the second hole transport region includes a second hole transport layer and a second electron blocking layer; the second electron transport region includes a second hole blocking layer, a second electron transport layer and an electron injection layer.

[0054] Furthermore, the light-emitting layer is composed of a main material and a doping material, and the main material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.

[0055] The deuterated organic compound of the present invention can be used in one or more layers of the above-mentioned organic electroluminescent device, preferably used as the n-type charge generation layer material of the device.

[0056] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts light-emitting materials and doping materials commonly used in the art, for example, it can be composed of a main material and a doping material. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as Liq, LiF, Yb, etc. The n-type charge generation layer material adopts the deuterated organic compound provided by the present invention. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).

[0057] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows: Device Example 1 The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10 -7 torr.

[0058] Subsequently, the following operations were performed: first, on the ITO layer (anode) formed on the substrate, a compound HTL-1 and a compound p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 was 97:3) were vacuum deposited at a thickness of 10 nm to form a hole injection layer; secondly, on the hole injection layer, a compound HTL-1 was vacuum deposited at a thickness of 20 nm to form a first hole transport layer; secondly, on the first hole transport layer, a compound EB-1 was vacuum deposited at a thickness of 5 nm to form a first electron blocking layer; and thirdly, on the first electron blocking layer, a mixture of a compound BH-1 and a compound BD-1 was vacuum deposited at a thickness of 20 nm to form a first The first light-emitting layer is a luminescent layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then, on the first light-emitting layer, the compound HB-1 is vacuum deposited with a thickness of 5 nm to form a first hole blocking layer; then, on the first hole blocking layer, the compound ETL-1 and the compound Liq (the mass ratio of ETL-1 to Liq is 1:1) are vacuum deposited with a thickness of 15 nm to form a first electron transport layer; then, on the first electron transport layer, the compounds C1 and Yb (the mass ratio of C1 to Yb is 98:2) are vacuum deposited with a thickness of 15 nm to form an n-type charge generation layer, and the compounds HTL-1 and Compound p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 is 97:3) is used to form a p-type charge generation layer, and then on the hole generation layer, compound HTL-1 is vacuum deposited with a thickness of 20 nm to form a second hole transport layer, and then on the second hole transport layer, compound EB-1 is vacuum deposited with a thickness of 5 nm to form a second electron blocking layer, and then on the second electron blocking layer, a mixture of compound BH-1 and compound BD-1 is vacuum deposited with a thickness of 20 nm to form a second light-emitting layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then on the second On the second light-emitting layer, compound HB-1 was vacuum deposited with a thickness of 5 nm to form a second hole blocking layer; then on the above second hole blocking layer, compound ETL-1 and compound Liq (the mass ratio of ETL-1 to Liq is 1:1) were vacuum deposited with a thickness of 15 nm to form a second electron transport layer; then on the above second electron transport layer, Yb was deposited with a thickness of 1 nm to form an electron injection layer, and then on the above electron injection layer, Mg and Ag (the mass ratio of Mg to Ag is 1:9) were deposited with a thickness of 15 nm to form a cathode, and then on the above cathode, compound CPL-1 was deposited with a thickness of 50 nm to form a covering layer, so as to prepare a stacked organic electroluminescent device.

[0059] In addition to the materials used in the present invention, the molecular structures of the remaining materials in each layer of the device are as follows:

[0060] Device Examples 2-11 The above method is used to prepare the compound described in the example into an organic electroluminescent device, wherein C2 to C11 are used to replace C1 to prepare organic electroluminescent device examples 2-11.

[0061] Device Comparison Examples 1-5 The above method was used to prepare the compounds described in the examples into organic electroluminescent devices, wherein D1-D5 were used to replace C1 to prepare organic electroluminescent device comparative examples 1-5.

[0062] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage, brightness, electroluminescent current efficiency (measured in cd / A) and external quantum efficiency (EQE, measured in percentage) of the organic electroluminescent device are determined at a current density of 200 mA / cm2, which is calculated from the current / voltage / luminescent density characteristic line (IVL characteristic line) showing Lambertian emission characteristics as a function of luminous density. The lifetime LT is defined as the time after which the brightness drops from the initial luminous brightness L0 to a specific proportion L1 when operating at a constant current J; J = 20 mA / cm2 2 The expression L1 = 90% means that at 20 mA / cm 2 When working under LT, the luminance drops to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm 2 , L1 = 95% means, at 20mA / cm 2 When working under LT, the luminous brightness drops to 95% of its initial value L0 after time LT.

[0063] The data of various OLED devices are summarized in Table 2. Various parameters of the device examples and the device comparative examples are compared to show the performance data of various OLED devices.

[0064] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows: Quantum efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-635; Current density and lighting voltage: tested using a digital source meter Keithley 2400; Blue index is obtained by dividing the quantum efficiency CE (cd / A) by the color coordinate (CIEy); Life test: Use LT-96ch life test device.

[0065] Table 2

[0066] From the above device performance test results, it can be seen that by increasing the material dissociation energy, reducing the material HOMO energy level, and improving the material molecular orientation, the organic material of the present invention is used in an organic electroluminescent device, and the driving voltage is significantly reduced compared with the comparative example, and the efficiency and life are improved to varying degrees. In particular, after adding a spacer, the life of the material is significantly increased. Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A compound having a phenanthroline structure, characterized in that, The compound is selected from the structure shown in the following formula I: I; Wherein, the ring A, ring B, and R2 are each independently selected from any one of phenyl, biphenyl, or naphthyl; The R1 is selected from one of the following structures: 、 、 、 、 、 、 、 、 、 、 、 、 ; In Formula I, at least one hydrogen may be substituted with deuterium, at least one nitrogen may be substituted with nitrogen-15, at least one oxygen may be substituted with oxygen-17 or oxygen-18, and at least one carbon may be substituted with carbon-13.

2. The compound according to claim 1, characterized in that The structure shown in Formula I is selected from one of the structures shown in Formula I-1 to Formula I-4 below: I-1、 I-2、 I-3、 I-4。 3. The compound according to claim 2, characterized in that The R1 is selected from one of the following structures: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 4. The compound according to claim 2, characterized in that The R1 is selected from one of the following structures: 、 、 。 5. The compound according to claim 2, characterized in that The R2 is selected from one of the following structures: 、 、 、 、 、 、 。 6. The compound according to claim 1, characterized in that The compound is selected from one of the structures shown below: 。 7. Use of the compound according to any one of claims 1 to 6 in the preparation of an organic electroluminescent device.

8. An organic electroluminescent device, characterized in that: It includes an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more compounds as described in any one of claims 1 to 6.

9. The organic electroluminescent device according to claim 8, characterized in that: The charge generation region comprises an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer comprises one or more compounds according to any one of claims 1 to 6.

10. A display device, characterized in that The display device comprises the organic electroluminescent device according to claim 8 or 9.

Citation Information

Patent Citations

  • Organic compound, organic light emitting diode and organic light emitting display device including the same

    CN108017672A

  • Light emitting device and electronic device including the same

    CN114975835A

  • Compound containing triazine and phenanthroline structure, organic electroluminescent device and laminated organic electroluminescent device

    CN116969935A

  • Phenanthroline derivative and organic electroluminescent device comprising same

    CN117024427A

  • Anthracene compound and organic electroluminescent device containing same

    CN117777094A